ORGANIZATION OF INTERNATIONAL CARGO TRANSPORTATION BY MAIN TYPES OF TRANSPORT (REVIEW) - Novak, Valentyna; Kyrylenko, Oksana; Razumova, Kateryna; Ihgnatiuk, Viktoria (Science-based technologies, 2022)
The article examines the turnover in international traffic, as well as identifies the reasons for its decline. Rolling stock and the fleet that delivers goods are analyzed. The main types of railway cars are: covered cars, gondola cars, platforms, tanks, isothermal cars. The specifics of the organization of international railway connections by two types of transport are considered. It is established that the participation of railway transport in the transport provision of mixed mass delivery systems, which currently form the structure of domestic exports, is especially significant. For a significant part of domestic exports, the use of rail transport to ensure the transportation of goods to seaports is unalterable. Among the export cargoes that can be transported through the territory of Ukraine are: foodstuffs, coal, automobile equipment, chemicals.The most important of the domestic seaports are the nearby ports of Odessa, the port of Chernomorsk and the South the so-called ports of "Greater Odessa". It is the share of these three ports that accounts for almost ⅔ of the total volume of cargo exported by sea.It is proved that the market of international freight transportation can be represented in terms of types of rolling stock in which goods are transported (types of ships, types of cars) and in terms of customs posts at the border. Measures are proposed to improve the situation on the market of international trucking: overcoming negative external factors, ie political and social instability; improving the quality characteristics of domestic goods; creation of the state long-term concept and policy of actions in the field of restoration of external relations and its regulation; improving product quality and reducing inflation in the Ukrainian economy.